2018
DOI: 10.1186/s12885-018-4146-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive expression of Midkine predicts early recurrence and poor prognosis of initially resectable combined hepatocellular cholangiocarcinoma

Abstract: BackgroundPost-surgical prognosis is usually poor for combined hepatocellular cholangiocarcinoma (CHCC-CC), a rare primary liver cancer. Although midkine (MK) is a prognostic biomarker for several known cancers, it is not known whether it can be used as such in resectable CHCC-CC. This study examined whether MK expression can predict recurrence and survival in patients with resectable CHCC-CC.MethodsWe retrospectively enrolled 52 patients with resectable CHCC-CC who had received curative hepatic resections. MK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In addition, there was no a TNM stage system which is specially designed for CHCC. It was reported that the differences of clinical features among CHCC, HCC and ICC could lead to the variations of prognostic factors [12, 13]. There were also many factors, such as age, gender and tumor grade, which were shown to have great impact on survival.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was no a TNM stage system which is specially designed for CHCC. It was reported that the differences of clinical features among CHCC, HCC and ICC could lead to the variations of prognostic factors [12, 13]. There were also many factors, such as age, gender and tumor grade, which were shown to have great impact on survival.…”
Section: Introductionmentioning
confidence: 99%
“…Even following treatment for localized disease it is common for the disease to recur, often with unresectable regional or distant/metastatic disease; ( 4 , 40 , 76 , 78 ) tumor recurrence rates at 1, 3, and 5 years were 60.8, 71.8, and 80.7%, respectively in one study, and median disease-free survival of 10 months has been reported ( 4 , 5 , 69 , 78 ). Recurrence rates seem to be non-significantly different in comparison to HCC and ICC, but mOS after recurrence tends to be worse than HCC and possibly worse than ICC ( 4 , 5 , 78 ).…”
Section: Treatmentmentioning
confidence: 99%
“…In patients with localized cHCC-ICC and good performance status, surgical resection may provide the chance of long-term benefit, for example, 5 year survival rate of 30% has been reported ( 12 , 68 , 69 ). These tumors show locoregional spread in similar patterns to HCC (hepatic and portal venous invasion) and to ICC (lymph node dissemination).…”
Section: Treatmentmentioning
confidence: 99%
“…Previous studies reported early recurrence (ER) (ie, recurrence within 2 years after surgery) rate of 57-75% and 6-months recurrence rate of about 40% or so. 6,7,[9][10][11] Therefore, the research on VER of cHCC is of vital importance.…”
Section: Introductionmentioning
confidence: 99%